ANALISIS TINGKAT PARTISIPASI MASYARAKAT DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA DI DESA CIKURA KECAMATAN BOJONG KABUPATEN TEGAL - Rifky Tri Amanah; Augustin Rina Herawati; Teuku Afrizal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The participation of the community in the Village Development Planning Meeting plays an important role in integrating the interests of the community, ensuring that the community's interests are included in village development, and ensuring accountability in the management of village funds so that the funds are used effectively and efficiently in accordance with the agreed-upon village development plan. This study aims to determine the level of community participation in the planning meeting and to identify the supporting and inhibiting factors of participation. The study uses a descriptive qualitative method. The results of interviews, observations, and review of documents related to Analysis of Community Participation Levels in Village Development Planning Meetings in Cikura Village, Bojong District, Tegal Regency will be identified using the concept of participation level according to Sherry Asrnstein (in Gates & Stout, 2000: 2)., namely there are eight levels of community participation. which is then subdivided into three degrees of participation, the first is Non Participation, the second is the Degree of Tokenism, then the third degree is Citizen Power.The results of this study indicate that the level of community participation in the village development planning meeting in Cikura Village reached the sixth step, which is Placation or the degree of tokenism. Factors that influence community participation include awareness, level of education, financial resources, occupation, socialization, and infrastructure.